Involvement of Lamin B1 Reduction in Accelerated Cellular Senescence during Chronic Obstructive Pulmonary Disease Pathogenesis - Nayuta Saito; Jun Araya; Saburo Ito; Kazuya Tsubouchi; Shunsuke Minagawa; Hiromichi Hara; Akihiko Ito; Takayuki Nakano; Yusuke Hosaka; Akihiro Ichikawa; Tsukasa Kadota; Masahiro Yoshida; et al. (2019)
Downregulation of lamin B1 has been recognized as a crucial step for development of full senescence. Accelerated cellular senescence linked to mechanistic target of rapamycin kinase (MTOR) signaling and accumulation of mitochondrial damage has been implicated in chronic obstructive pulmonary disease (COPD) pathogenesis. We hypothesized that lamin B1 protein levels are reduced in COPD lungs, contributing to the process of cigarette smoke (CS)-induced cellular senescence via dysregulation of MTOR and mitochondrial integrity. To illuminate the role of lamin B1 in COPD pathogenesis, lamin B1 protein levels, MTOR activation, mitochondrial mass, and cellular senescence were evaluated in CS extract (CSE)-treated human bronchial epithelial cells (HBEC), CS-exposed mice, and COPD lungs. We showed that lamin B1 was reduced by exposure to CSE and that autophagy was responsible for lamin B1 degradation in HBEC. Lamin B1 reduction was linked to MTOR activation through DEP domain-containing MTOR-interacting protein (DEPTOR) downregulation, resulting in accelerated cellular senescence. Aberrant MTOR activation was associated with increased mitochondrial mass, which can be attributed to peroxisome proliferator-activated receptor γ coactivator-1β-mediated mitochondrial biogenesis. CS-exposed mouse lungs and COPD lungs also showed reduced lamin B1 and DEPTOR protein levels, along with MTOR activation accompanied by increased mitochondrial mass and cellular senescence. Antidiabetic metformin prevented CSE-induced HBEC senescence and mitochondrial accumulation via increased DEPTOR expression. These findings suggest that lamin B1 reduction is not only a hallmark of lung aging but is also involved in the progression of cellular senescence during COPD pathogenesis through aberrant MTOR signaling.